THE INFLUENCE OF WORK MOTIVATION, COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE (CASE STUDY AT MATAHARI DEPARTMENT STORE PARAGON SEMARANG) - Yuliati, Yuliati; Wahyuningsih, Susanti; Widodo, Untung; Indriyatni, Lies; Widowati, Madurento (STIE Pelita Nusantara Semarang, 2024)
This research aims to determine the influence of the variables Work Motivation, Compensation and Work Disciplin on Employee Performance at Matahari Departement Store Paragon Semarang. The research is a quantitative study using 105 responden from Matahari Departement Store employees in the sales promotion section. The method used is multiple linear regression SPSS program version 23. Multiple linear regression analysis technique Y = α + β1X1 + β2X2 + β3X3 + e. The research data variable is Employee Performance (Y) and X is Work Motivation, Compensation and Work Disciplin. The results of the Work Motivation (X1) have positive and significant influence on Employee Performance with t count 1,660), with a significance value of 0.000 t table (9,336>1,660), with a significance value of 0.000 t table (2,823>1,660), with a significance value of 0.006 F table (72,401 >2.699) with a significance of 0.000. Calculation of the value of the Coefficient of Determination (R2) obtained Adjusted R2 of 0,673. This means that the percentage of the influence of the variable Work Motivation, Compensation and Work Disciplin on Employee Performance is 67,3 %, while the remaining 32.7% is influenced or explained by other factors.